Self‐injurious behaviours in children and adults with autism spectrum disorder (ASD). Issue 12 (25th April 2018) - Gulsrud, A.; Lin, C. E.; Park, M. N.; Hellemann, G.; McCracken, J.
Abstract: Background: Self‐injurious behaviours (SIB) are concerning, maladaptive behaviours that commonly occur in people with neurodevelopmental conditions and delays but seem to be particularly prevalent in children and adults with autism spectrum disorder (ASD). There has been increasing research examining the risk markers associated with the presence of SIB in people with ASD. Some of the factors associated with SIB have included cognitive abilities, adaptive functioning deficits and behaviour regulation impairments (e.g. impulsivity and repetitive behaviours). However, many of the findings in the literature are mixed and only explain a small proportion of the variance contributing to SIB. Limitations in the previous literature have centred on lack of availability of large and diverse samples, restricted age ranges and constraints of measurement. Method: This study characterises a clinic‐referred sample of children and adults currently presenting with and without SIB using a range of standardised and parent‐report measures. The sample includes 144 individuals with ASD between the ages of 2.5 and 60.1 years. Results: After adjusting for multiple tests, none of the variables maintained statistical significance between the group of individuals with and without SIB, but medium to large effect sizes were noted. These variables include parent‐reported early motor and toileting delays and perinatal risk, and current cognitive and social impairment. The remaining variables, including current autism severity levels, early ASD symptomatology, impulsivity, executive functioning impairments, adaptive functioning, mood and anxiety, did not differ between those with and without current engagement in SIB. Conclusions: Utilising a diverse clinic‐referred sample and standardised diagnostic tools, this study explored retrospective and current correlate risk markers of SIB in individuals with ASD. In addition to impairments in current functioning, specific early developmental delays and perinatal risk factors were preliminarily associated with the presence of SIB in individuals with ASD. Together these findings suggest that a set of specific characteristics may be related to both early risk and concurrent manifestation of SIB. Identifying this set of characteristics in early development may lead to faster identification and better intervention services, but future work utilising longitudinal design and multivariate analysis is warranted.